Evidences of +896 A/G TLR4 Polymorphism as an Indicative of Prevalence of Complications in T2DM Patients - Carmela Rita Balistreri; Anna Rita Bonfigli; Massimo Boemi; Fabiola Olivieri; Antonio Ceriello; Stefano Genovese; Claudio Franceschi; Liana Spazzafumo; Paolo Fabietti; Giuseppina Candore; Calogero Caruso; Domenico Lio; et al. (Mediators of Inflammation)
T2DM is today considered as world-wide health problem, with complications responsible of an enhanced mortality and morbidity. Thus, new strategies for its prevention and therapy are necessary. For this reason, the research interest has focused its attention on TLR4 and its polymorphisms, particularly the rs4986790. However, no conclusive findings have been reported until now about the role of this polymorphism in development of T2DM and its complications, even if a recent meta-analysis showed its T2DM association in Caucasians. In this study, we sought to evaluate the weight of rs4986790 polymorphism in the risk of the major T2DM complications, including 367 T2DM patients complicated for the 55.6%. Patients with A/A and A/G TLR4 genotypes showed significant differences in complication’s prevalence. In particular, AG carriers had higher risk prevalence for neuropathy (P=0.026), lower limb arteriopathy (P=0.013), and the major cardiovascular pathologies (P=0.017). Their cumulative risk was significant (P=0.01), with a threefold risk to develop neuropathy, lower limb arteriopathy, and major cardiovascular events in AG cases compared to AA cases. The adjusted OR for the confounding variables was 3.788 (95% CI: 1.642–8.741). Thus, the rs4986790 polymorphism may be an indicative of prevalence of complications in T2DM patients.